Use of vegetation for slope protection: Root mechanical properties of some tropical plants - Ali, F. (Academic Journals, 2010)
It is well documented that a bioengineering approach has recently regained a global recognition in preventing and controlling surface run-off, erosion and landslides. However, there is a lack of documentation on the root mechanical properties available especially in Malaysia. In this study, both pull-out and tensile strength of some tropical plants namely Leucaena leucocephala, Acacia mangium and Melastoma malabathricum is investigated on different stem sizes. Plots of pull-out capacity against displacement in L. leucocephala exhibit the presence of two peak values. Closer examination concludes that the first peak indicates the failure of the lateral roots and the second peaks is achieved when the tap roots failed. As for the tensile strength tests, results showed that the tensile strength decreases with increasing root diameter. The results also indicate that there is no correlation observed between the tensile strength, root length and root moisture content. Amongst the species, the highest root tensile strength was observed in L. leucocephala, followed by A. mangium and M. malabathricum. Thus, the study suggests that L. leucocephala is the best choice for slope stabilization work as it exhibits outstanding root mechanical properties.